Plasmonic Y-splitters of High Wavelength Resolution Based on Strongly Coupled-Resonator Effects - Chen, Jianjun; Li, Zhi; Ming Lei; Fu, Xiuli; Xiao, Jinghua; Qihuang Gong (PLASMONICS, 2012)
Based on the strongly coupled-resonator effects, a high wavelength-resolution plasmonic Y-splitter, consisting of a Y-branch metal-insulator-metal waveguide with a baffle in each channel, is numerically investigated using the finite element method. Due to the coupling of different resonators (with nearly equal bandwidths) in the Y-splitter, sharp and asymmetric transmission spectra occur. This greatly increases the wavelength resolution of the Y-splitter to be Delta lambda a parts per thousand aEuro parts per thousand 15 nm, which is significantly narrower than the bandwidth of the single resonator (Delta lambda (FWHM) a parts per thousand aEuro parts per thousand 110 nm). An analytic model based on the scattering matrix theory is provided to describe and explain this phenomenon.
Keywords: Asymmetric spectra; Coupled-resonator system; Scattering matrix theory; surface plasmon polaritons